ANTI-HYPERCHOLESTEROLEMIC AND ANTI-ATHEROGENIC ACTIVITY OF Terminalia chebula FRUIT IN NORMAL AND CHOLESTEROL FED RABBITS - K. M. Anjum; U. Sayyed; Aziz Ullah; M.S. Mughal; A. Yaqub; M.A. Rashid; M. Z. Yousaf (Journal of Animal and Plant Sciences, 2014)
Over the centuries plants have been effectively used as a potent source of traditional medicine. Present experiment was aimed to evaluate the hypocholesterolemic and anti-atherogenic effect of feeding Terminalia chebula powder (TCP)in rabbits. A total of (n=20) rabbits were assigned to four treatment groups with n=5 animals in each group. Experimental treatments received Normal Saline (NS); T. chebula powder (TCP), high fat diet (HFD) and high fat diet plus T. chebula powder (HFDTCP). Blood samples were taken on a weekly basis to diagnose the effects of test drug on serum Total Cholesterol (TC), LDL, HDL, Triglycerides (TG) and Atherogenic Index. All the parameters were measured in mg/dl except the atherogenic index measured in units. In HFD rabbits TC (362.59±6.00), LDL (262.59±6.12) triglycerides (258.7±2.90) and atherogenic index (13.50±1.20) was higher (p <0.05), while HDL (25.73±1.09) was significantly reduced to an alarming level at the end of eight weeks. When HFD rabbits were treated with TCP for eight weeks, TC (132.60±4.93), LDL (89.13±2.75), Triglycerides (125.86±9.06) and atherogenic index (1.54±0.03) reduced significantly and increased (p <0.05) the HDL (52.10±1.50). It was therefore concluded that that T. chebula powder can safely be used to reduce bad cholesterol (LDL) and to enhance good cholesterol (HDL).
Keywords: Medicinal plants; Terminalia chebula; HDL; LDL; Hypercholesteremia; Atherogenic Index